2010
DOI: 10.1016/j.vetpar.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the hair of owned dogs with the eggs of Toxocara spp.

Abstract: Please cite this article as: Keegan, J.D., Holland, C.V., ontamination of the hair of owned dogs with the eggs of Toxocara spp., Veterinary Parasitology (2008Parasitology ( ), doi:10.1016Parasitology ( /j.vetpar.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 14 publications
2
34
1
1
Order By: Relevance
“…None of the eggs found on the coat of the positive animals was viable, probably a result of UV-light and/or lack of humidity (Overgaauw et al 2009). This result fits with the low percentage of embryonated roundworm eggs found in similar studies carried out in the Netherlands and in the UK (Overgaauw et al 2009;Keegan and Holland 2010). This work reports, for the first time, the presence of T. vulpis eggs on the coat of a dog (Table 1), but the significance of this finding is unclear pending that the zoonotic potential of the dog whipworm is clarified.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…None of the eggs found on the coat of the positive animals was viable, probably a result of UV-light and/or lack of humidity (Overgaauw et al 2009). This result fits with the low percentage of embryonated roundworm eggs found in similar studies carried out in the Netherlands and in the UK (Overgaauw et al 2009;Keegan and Holland 2010). This work reports, for the first time, the presence of T. vulpis eggs on the coat of a dog (Table 1), but the significance of this finding is unclear pending that the zoonotic potential of the dog whipworm is clarified.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to the two trichuroids here found, the role of T. vulpis as a zoonotic agent is still unclear (Traversa 2011), while C. aerophila is capable of inducing, though rarely, the human lung capillariosis, characterized by fever, bronchitis, cough, hemoptysis, dyspnea, and which can mimic the symptoms of a bronchial carcinoma (Lalosević et al 2008). The percentage of animals whose coat resulted contaminated by parasite eggs is lower than the number expected based on previous works (Wolfe and Wright 2003;Roddie et al 2008;Aydenizöz-Ozkayhan et al 2008;Overgaauw et al 2009;Keegan and Holland 2010). None of the eggs found on the coat of the positive animals was viable, probably a result of UV-light and/or lack of humidity (Overgaauw et al 2009).…”
Section: Discussionmentioning
confidence: 76%
“…It is reported that age is not related with the contamination of Toxocara eggs of the hair (29,30,36) or in other words the eggs on the hair can be seen in all age groups but it is more common in less than one year old (2,4,14,20). The result of the present study suggest that puppies are more likely to harbour eggs on their hair than young and adult.…”
Section: Discussionmentioning
confidence: 40%
“…Recent studies have found embryonated T. canis eggs on the hair of dogs which suggested that direct contact with dogs may be important risk factor (4,14,20,28,36). Regarding Toxocara spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation